1998
DOI: 10.1007/pl00000098
|View full text |Cite
|
Sign up to set email alerts
|

Revision of the Assigned Structures of 5- and 7-Iodo-8-quinolinols and 5-and 7-Iodo-2-methyl-8-quinolinols

Abstract: Revised structures are presented for 5-and 7-iodo-8-quinolinols and for 5-and 7-iodo-2-methyl-8-quinolinols based on NMR studies. UV spectroscopic characterization of the compounds was also carried out.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1998
1998
2003
2003

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 6 publications
(15 reference statements)
0
1
0
Order By: Relevance
“…Carke confirmed that C-5 was iodinated and provided us NMR data. 3 When ethanolic solutions of 1 or 2 were slowly condensed at room temperature, single crystals suitable for an X-ray diffraction method were obtained. Intensity data were collected and corrected for both Lorentz and polarization effects.…”
mentioning
confidence: 99%
“…Carke confirmed that C-5 was iodinated and provided us NMR data. 3 When ethanolic solutions of 1 or 2 were slowly condensed at room temperature, single crystals suitable for an X-ray diffraction method were obtained. Intensity data were collected and corrected for both Lorentz and polarization effects.…”
mentioning
confidence: 99%